Clinical and Dermoscopic Characteristics of Cutaneous Chondroid Syringoma: A Systematic Review - Antonio Di Guardo; Charalampos G Balampanos; Luca Gargano; Domenico Giordano; Alessandro Capalbo; Flavia Persechino; Severino Persechino (Mattioli1885, 2024)
Introduction: Cutaneous chondroid syringoma (CS) is a rare benign mixed skin tumor originating from sweat glands. Despite its rarity, accurate diagnosis and management are crucial due to its potential for malignant transformation. Objective: This study aims to provide comprehensive insights into the main features of cutaneous CS, encompassing its epidemiology, clinical presentation, and particularly, dermoscopic findings. Methods: A systematic review was conducted to identify relevant literature on CS up to November 2023. Data extraction included clinical and histopathological characteristics from case reports and small case series. Results: The systematic review identified 347 unique CS cases, predominantly benign. Clinical features included a predilection for the head and neck region, with variations in morphology observed. Dermoscopic patterns, although limited, revealed recurrent features aiding diagnosis. Malignant CS cases constituted a notable subset, exhibiting distinct clinical and histopathological features. Conclusion: Cutaneous chondroid syringoma presents with characteristic clinical and histopathological features, necessitating comprehensive diagnostic approaches. Dermoscopy emerges as a valuable tool, although further research is needed to establish definitive patterns. Treatment primarily involves wide local excision, with collaboration among clinicians essential for optimal management. Future studies are warranted to address existing knowledge gaps and enhance understanding of this rare skin neoplasm.